OCD? Not Me! Protocol for the development and evaluation of a web-based self-guided treatment for youth with obsessive-compulsive disorder. Issue 4 (29th April 2015) - Rees, Clare S; Anderson, Rebecca A; Finlay-Jones, Amy
Abstract : Background: OCD? Not Me! is a novel, web-based, self-guided intervention designed to treat obsessive-compulsive disorder (OCD) in young people aged 12–18, using the principles of exposure and response prevention. The current paper presents the protocol for the development of the programme and for an open trial that will evaluate the effectiveness of this programme for OCD in young people, and associated distress and symptom accommodation in their parents and caregivers. Methods: We will measure the impact of the OCD? Not Me! programme on OCD symptoms using the Children's Florida Obsessive Compulsive Inventory (C-FOCI), and both the self-report and parent report of the Children's Obsessional Compulsive Inventory—Revised (ChOCI-R). The impact of the programme on OCD-related functional impairment will be measured using the parent report of the Child Obsessive-Compulsive Impact Scale—Revised (COIS-R). Secondary outcome measures include the Rosenberg Self-Esteem Scale and the Youth Quality of Life—Short Form (YQoL-SF). The 21-item Depression Anxiety Stress Scales (DASS-21) will be used to measure the impact of the programme on parent/caregiver distress, while the Family Accommodation Scale (FAS) will be used to measure change in family accommodation of OCD symptoms. Multilevel mixed effects linear regression will be used to analyse the impact of the intervention on the outcome measures. Ethics and dissemination: This study has been approved by the Curtin University Human Research Ethics Committee. The results of the study will be reported in international peer-reviewed journals. Trial registration number: Australian New Zealand Clinical Trials Registry: ACTRN12613000152729.